The Legal Position Of Electronic Medical Recording As An Evidence At The Court - Dwi Retno Wulandari (Ius Poenale, 2021)
This research aimed to analyze the position of electronic medical records and as evidence in court. The research method uses a normative juridical approach. To obtain an overview of electronic medical records as evidence in court, the legal materials collected are qualitative data. Any electronic evidence can be used as evidence if it meets formal and material requirements, as regulated in Article 5 paragraph (4) of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law). Electronic medical records have an essential role in health services and law enforcement efforts as evidence. Based on this, the main problem is the position of electronic medical records as valid evidence in court. The results show that the position of electronic medical records as evidence in court can be valid evidence following Article 184 of the Criminal Procedure Code (KUHAP), The Ministry of Health Regulation 269/2008 Articles 5 and 1, Article 51 of Government Regulation No. 71 Years. As evidence, electronic medical records do not have binding evidentiary power but rather have independent evidentiary value, namely, proof determined by the judge's conviction without being limited by law.